Production of Disinfectant Using Aloe Vera (Aloe barbadensis miller) Plant Extracts - C. P Ukpaka (International Journal of Pollution: Prevention & Control, 2023)
This research work demonstrates the production of a disinfectant using aloe vera (Aloe barbadensis Miller) as main source of the raw material. The liquid content of the aloe vera was extracted using mechanical and unit operation mechanisms and the obtained raw material was subjected to heating to evaluate the effect of temperature on the characteristics of the physiochemical properties of pH, total ash, crude fat, fibre and protein, total carbohydrate, dehydration ratio (gas water) and water holding capacity. The effect of temperature was observed as demonstrated in this research work. Increase and decrease were observed in considering the functional parameters of flash point, viscosity, pour point, specific gravity, boiling range, and pH. The result obtained using aloe vera was compared with existing ones and show a good match, indicating that the end product can be used as disinfectant. The bio disinfectant had a pH of 8.32, specific gravity of 0.9744, viscosity of 2. 310 Pa s at 25℃, boiling range of 54℃ and a flash point of 57℃, while the existing disinfectant had a pH of 9.5, specific gravity 0.98, viscosity of 2. 4 Pa s at 25℃, boiling range of 85℃ and a flash point of 57.5℃. Keywords: Production, disinfectant, aloe vera, Aloe barbadensis Miller, plant extracts
Keywords: Aloe Barbadensis miller; Aloe vera; Disinfectant; Plant extracts; production